2012
DOI: 10.3748/wjg.v18.i33.4585
|View full text |Cite
|
Sign up to set email alerts
|

Spectral analysis of bowel sounds in intestinal obstruction using an electronic stethoscope

Abstract: Auscultation of bowel sounds is non-specific for diagnosing bowel obstruction. Differences in sound characteristics between large bowel and small bowel obstruction may help determine the likely site of obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 19 publications
3
46
1
Order By: Relevance
“…sounds in intestinal obstruction using an electronic stethoscope. They found that bowel sound characteristics were not different among patients with acute, subacute or no intestinal obstruction using the commonly compared parameters including sound duration, sound-to-sound interval, and dominant and peak frequencies (12). In another study, the authors concluded that auscultation of bowel sounds is not a useful clinical practice when differentiating patients with normal versus pat hologic bowel sounds (13).…”
Section: Discussionmentioning
confidence: 98%
“…sounds in intestinal obstruction using an electronic stethoscope. They found that bowel sound characteristics were not different among patients with acute, subacute or no intestinal obstruction using the commonly compared parameters including sound duration, sound-to-sound interval, and dominant and peak frequencies (12). In another study, the authors concluded that auscultation of bowel sounds is not a useful clinical practice when differentiating patients with normal versus pat hologic bowel sounds (13).…”
Section: Discussionmentioning
confidence: 98%
“…Bowel sounds are also important, for their clinical correlations with intestinal function. 173 Wang et al 174 have developed a flexible wearable wireless device for long-term and real-time monitoring of bowel sounds, which transmits the sound signal to the mobile handset through Bluetooth for waveform display as shown in Fig. 9c.…”
Section: Strain and Pressurementioning
confidence: 99%
“…Judgements regarding the presence of "normal," "decreased," or "asthenic" intestinal murmurs is subjective, and definitive criteria have yet to be established for the evaluation of intestinal murmurs by auscultation. Furthermore, studies have reported a low rate of agreement between observers [60,61] (level 4), [62][63][64] (level 3).…”
Section: Cq38 Does Abdominal Examination Using a Stethoscope Have Utimentioning
confidence: 99%